Culture shock and Japanese-American relations historical essays - Asada, Sadao, 1936- (University of Missouri Press, 2007)
"Examines historical episodes in the interactions between the United States and Japan from 1890 to 2006, focusing on naval stategy before and during World War II and transpacific racism. Asada analyes both American and Japanese perceptions of Pearl Harbor and the atomic bomb controversy"--Provided by publisher.